2018
DOI: 10.3892/etm.2018.6295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine as an adjunct in transversus abdominis plane block during gynecological laparoscopy

Abstract: Ultrasound-guided transversus abdominis plane (TAP) block for abdominal surgery has been widely studied in clinical settings. However, dexmedetomidine as an adjunctive analgesic combined with TAP block has been rarely reported. The present study evaluated the efficacy of TAP block combined with dexmedetomidine adjunct for gynecological laparoscopy. In brief, 90 patients were randomly divided into three groups: Group I, which received post-operative intravenous analgesia only after general anesthesia; Group II,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Also, it is widely used as an adjuvant for the perineural nerve block. When DEX is combined with a local anesthetic agent for TAP block, it can prolong the duration of block [31] or improve postoperative pain and recovery from anesthesia [32], which is possibly due to local vasoconstriction in peripheral nerves [33] or direct inhibition in peripheral nerve action [34]. DEX was found to dose-dependent enhance of the local anesthetic effect of lidocaine in rats [35] and in healthy volunteers [36].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is widely used as an adjuvant for the perineural nerve block. When DEX is combined with a local anesthetic agent for TAP block, it can prolong the duration of block [31] or improve postoperative pain and recovery from anesthesia [32], which is possibly due to local vasoconstriction in peripheral nerves [33] or direct inhibition in peripheral nerve action [34]. DEX was found to dose-dependent enhance of the local anesthetic effect of lidocaine in rats [35] and in healthy volunteers [36].…”
Section: Discussionmentioning
confidence: 99%
“…Almarakbi et al ( 16 ) also observed that the addition of dexmedetomidine to bupivacaine in TAP block achieves better local anaesthesia and provides better pain control postoperatively without any major side effects in open abdominal hysterectomy. Xue et al ( 20 ) in their study had also observed that the USG-guided TAP block combined with dexmedetomidine as adjuvant improves recovery from anaesthesia and reduces postoperative pain during gynaecological laparoscopy. A recently published systematic review and meta-analysis by Sun et al ( 25 ) has concluded that dexmedetomidine as an adjuvant provides better postoperative analgesia in addition to reducing postoperative analgesic and prolonging the LA effect when administered in TAP blocks for abdominal surgery.…”
Section: Discussionmentioning
confidence: 93%
“…Dexmedetomidine, a highly selective α2 agonist, has been evaluated for its efficacy and safety in prolonging the duration of TAP block when added as an adjuvant in various surgical procedures ( 18 ). Many studies have found that the addition of dexmedetomidine to LAs in central neuraxial blocks and in peripheral nerve blocks is a safe and effective way to potentiate the LA effect and thus reduces the need for further analgesics, enhancing postoperative recovery ( 16 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…They confirmed its superior prolonged analgesia and the reduced need for additional backup analgesics when used with LA (Sarvesh et al., 2018). When it is combined with LA agents, it can prolong the duration of block or improve the postoperative pain and the recovery after anaesthesia (Xue et al., 2018). Dexmedetomidine has been recently searched for the same purpose with parallel results as an adjuvant to LA in different types of postoperative analgesia blocks in paediatric patients with a favourable analgesic profile than the LA alone (AlGhamdi et al., 2019; Mostafa, Aal, et al., 2020; Raof et al., 2017).…”
Section: Discussionmentioning
confidence: 99%